Fasciola hepatica excretory-secretory products attenuate demyelination and reduce neuroinflammation in the Cuprizone –induced multiple sclerosis model - Aliakbar Mariki; Kristi Anne Kohlmeier; Seyed Mohammad Mousavi; Alireza Keyhani; Majid Fasihi Harandi; Mansoureh Sabzalizadeh; Mohammad Shabani (PLoS ONE, 2026)
Multiple sclerosis (MS) is characterized by chronic neuroinflammation and progressive demyelination, with current therapies failing to adequately address both processes simultaneously. Helminth-derived excretory–secretory products (ESP) are immunomodulatory molecules that suppress host inflammation and are promising candidates for MS treatment. However, their capacity to promote remyelination remains poorly understood. This study investigated the effects of Fasciola hepatica ESP in the cuprizone-induced demyelination model. Male C57BL/6 mice were divided into four groups: control (CON), control + FES (CON + FES), cuprizone (CUP), and cuprizone + FES (CUP + FES). FES was administered intraperitoneally during the demyelination phase. Motor and cognitive functions were evaluated using open field, rotarod, wire grip, and shuttle box tests. Neuroinflammation was assessed by measuring TNF and IL-1β levels, while myelin-related changes were evaluated by MBP and Olig2 expression (ELISA and qPCR) and Luxol Fast Blue staining. FES treatment significantly reduced pro-inflammatory cytokines, increased MBP and Olig2 levels, improved myelin integrity, and enhanced motor and cognitive performance compared to untreated cuprizone mice, though full recovery to control levels was not achieved. These findings demonstrate that FES attenuates neuroinflammation and is associated with partial improvements in myelin-related outcomes in the cuprizone model, supporting the therapeutic potential of helminth-derived molecules for MS.